SiS Catalyst: CHildren as Agents of Change for Science and Society (2011)
For three years, EAFIT Children's University has been part of the European Network of Children's Universities. This is where EAFIT was invited to participate as an advisor to SiS Catalyst, a project developed by European networks and organizations that aims to promote the leading role of children and young people in the configuration of the content of educational programs that strengthen bond between science and society.